Characteristics of aroma compounds and selected factors shaping their stability in food with reduced fat content - Bortnowska, Grażyna (Charakterystyka substancji zapachowych oraz wybrane czynniki kształtujące ich stabilność w żywności o obniżonej zawartości tłuszczu, 2018)
Shaping the quality of food aroma as an important factor in product selection and acceptance is still the current goal of the conducted scientific research. Many studies indicate that the quality of aroma in the hedonistic category depends on the volatility and concentration of odorants that can cause extremely desirable or undesirable sensory sensations. In turn, indicators for assessing the impact of selected factors affecting the quality of food aroma are retention and the odor activity value (OAV). Food flavorings are preferred because of their standardized quality, strength of aroma and sterility, while super-spices due to their multifunctionality. The attention is also drawn to the growing interest in food emulsions as universal carriers of aroma compounds, and the possibility of shaping their stability in foods, especially those with reduced fat content, by appropriate selection of natural emulsifiers and/or thickeners
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2018, Nr 3 (30), s. 9-19
Keywords: low-fat foods; aroma compounds; flavorings; aroma quality; żywność niskotłuszczowa; substancje zapachowe; aromaty spożywcze; jakość zapachu